2018
DOI: 10.14419/ijet.v7i2.8.10336
|View full text |Cite
|
Sign up to set email alerts
|

Study of effects of blood alcohol consumption (BAC) level on drivers physiological behavior and driving performance under simulated environment

Abstract: Alcohol consumption impairs driving skills and responsible for a high proportion of traffic accidents. This research examined the effects of blood alcohol consumption (BAC) level on driver’s physiological behavior and driving performance under simulated driving environment. The participants consisted of eight healthy young male drivers with an average of eight years driving experience. The scenario considered was 5 min driving on a highway with different speed limits, crossings, and unexpected event. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This measurement was used as input to determine alcohol consumption under a simulated driving environment. The experiment results demonstrate that physiological data and driving performance can evaluate even a low dose of alcohol consumption of 0.03% BAC level [72].…”
Section: Drunk Driving Monitoringmentioning
confidence: 87%
“…This measurement was used as input to determine alcohol consumption under a simulated driving environment. The experiment results demonstrate that physiological data and driving performance can evaluate even a low dose of alcohol consumption of 0.03% BAC level [72].…”
Section: Drunk Driving Monitoringmentioning
confidence: 87%
“…For instance, it was observed that a concentration of 0.1‰ causes distraction 0.2‰ prolongs perceptual time, 0.3‰ impairs coordination and shape perception, 0.5‰ hinders judgement, 0.8‰ induces misjudgment of personal abilities, and a concentration exceeding 1.0‰ leads to impaired intellectual performance, delayed reaction time and instigates recklessness. The research in paper [34] evaluates drivers' reaction times in relation to blood alcohol concentration. The results showed that reaction times nearly doubled at a concentration of 1.5‰, with measurements based on braking distance of 50 km/h, and footage from two cameras.…”
Section: Introductionmentioning
confidence: 99%